Fabrication of core-shell, yolk-shell and hollow Fe3O4@ carbon microboxes for high-performance lithium-ion batteries - Tian, H.; Liu, H.; Yang, T.; Veder, J.; Wang, G.; Hu, M.; Wang, Shaobin; Jaroniec, M.; Liu, J. (CHINESE CHEMICAL SOC, 2017)
Metal oxide–carbon composites with core–shell, yolk–shell and hollow structures have attracted enormous interest because of their applications in lithium-ion batteries. However, the relationship between structure and battery performance is still unclear. Herein, we report the designed synthesis of unique core–shell, yolk–shell and hollow Fe3O4@carbon microboxes through a one-step Stöber coating method, followed by a carbonization process. Different calcination temperatures were investigated to manipulate the various structures, and the impact of layer thickness on the battery performance was also assessed. Our results showed that the core–shell structured Fe3O4@carbon microboxes with nitrogen-doped carbon shells having a thickness of 15 nm exhibited an excellent performance in lithium-ion batteries with a high reversible capacity of 857 mA h g−1 that could be retained after 100 cycles at a current density of 0.1 A g−1.